Involvement of the AcrAB-TolC Efflux Pump in the Resistance, Fitness, and Virulence of Enterobacter cloacae - Pérez, Astrid (American Society for Microbiology, 2012)
Multidrug efflux pumps have emerged as important mechanisms of antimicrobial resistance in bacterial pathogens. In order to cause infection, pathogenic bacteria require mechanisms to avoid the effects of host-produced compounds, and express efflux pumps may accomplish this task. In this study, we evaluated the effect of the inactivation of AcrAB-TolC on antimicrobial resistance, fitness, and virulence in Enterobacter cloacae, an opportunistic pathogen usually involved in nosocomial infections. Two different clinical isolates of E. cloacae were used, EcDC64 (multidrug resistance overexpressing the AcrAB-TolC efflux pump) and Jc194 (basal AcrAB-TolC expression). The acrA and tolC genes were deleted in strains EcDC64 and Jc194 to produce, respectively, EcΔacrA and EcΔtolC and JcΔacrA and JcΔtolC knockout (KO) derivatives. Antibiotic susceptibility testing was performed with all isolates, and we discovered that these mechanisms are involved in the resistance of E. cloacae to several antibiotics. Competition experiments were also performed with wild-type and isogenic KO strains. The competition index (CI), defined as the mutant/wild-type ratio, revealed that the acrA and tolC genes both affect the fitness of E. cloacae, as fitness was clearly reduced in the acrA and tolC KO strains. The median CI values obtained in vitro and in vivo were, respectively, 0.42 and 0.3 for EcDC64/EcΔacrA, 0.24 and 0.38 for EcDC64/EcΔtolC, 0.15 and 0.11 for Jc194/JcΔacrA, and 0.38 and 0.39 for Jc194/JcΔtolC. Use of an intraperitoneal mouse model of systemic infection revealed reduced virulence in both E. cloacae clinical strains when either the acrA or tolC gene was inactivated. In conclusion, the structural components of the AcrAB-TolC efflux pump appear to play a role in antibiotic resistance as well as environmental adaptation and host virulence in clinical isolates of E. cloacae.